2009
DOI: 10.1016/j.mito.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of synthetic diarylamines: A mitochondrial and cellular approach

Abstract: a b s t r a c tWe investigated the antioxidant properties of two synthetic diarylamines, MJQ1 and MJQ2. For one of them (MJQ1) the synthesis procedure is herein described. The compounds showed maximal protection of ADP/Fe 2+ induced mitochondrial lipid peroxidation for 50 nM (MJQ1) and 60 lM (MJQ2) concentrations. Both compounds were also effective in the prevention of mitochondrial DW collapse. The effective antioxidant dose of MJQ1 in mitochondria (50 nM) also proved to protect lipid peroxidation in PC12 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Both compounds 3 and 5 demonstrated antioxidative properties, although compound 3 less so than compound 5. This finding was not too surprising in light of reports that describe antioxidant properties of new agents structurally related to our compounds [41,42]. Interestingly, the reduced redox environment caused by antioxidant treatment stabilizes caspases and thus influences their activity and promotes the induction of apoptosis [43].…”
Section: Gene Ontologysupporting
confidence: 66%
“…Both compounds 3 and 5 demonstrated antioxidative properties, although compound 3 less so than compound 5. This finding was not too surprising in light of reports that describe antioxidant properties of new agents structurally related to our compounds [41,42]. Interestingly, the reduced redox environment caused by antioxidant treatment stabilizes caspases and thus influences their activity and promotes the induction of apoptosis [43].…”
Section: Gene Ontologysupporting
confidence: 66%
“…Although anilines have been known to exhibit red cell and liver toxicity, 28,29 interestingly, the diarylamines have been recently shown to play a beneficial role against oxidative stress. 30 In this preliminary communication we have shown that the secondary diarylamino moiety could be a viable functional group for the design of suitable type 1 photosensitizers. We have demonstrated that the photolysis of diarylamines generates reactive species that destroy the cancer cells.…”
mentioning
confidence: 97%
“…To be clinically useful, these diarylamines must not only absorb in the visible region but also display low systemic toxicity. Although anilines have been known to exhibit red cell and liver toxicity, , interestingly, the diarylamines have been recently shown to play a beneficial role against oxidative stress …”
mentioning
confidence: 99%
“…To further explore the utility of this new protocol, we also investigated the synthesis of diarylamines, which are described in the literature as important molecules due to their antioxidant capacity (Pinto-Basto et al, 2009). Preliminary experiments disclosed that, under the above experimental conditions, aniline ( 4a ) hardly coupled with bromobenzene ( 1a ) as the desired adduct 5aa was delivered in 5% yield only.…”
Section: Resultsmentioning
confidence: 99%